Bakau Serip Old Village: Integrating Nature, Culture and Culinary Delights in Sustainable Tourism - Annisa, Annisa Putri; Kafriatye, Anzala; Mokal, Mahvish Nawaz (Jeksyah: Islamic Economics Journal, 2024)
The purpose of this study is to evaluate the potential and formulate a strategy for developing a tourist village in Kampung Tua Bakau Serip in order to increase tourist visits. The methods used were field surveys, in-depth interviews, and SWOT analysis. Data were collected from 30 tourists, 10 local residents, and 5 tourism experts. The survey results were analyzed qualitatively. The results show that Kampung Tua Bakau Serip has tourist attractions in the form of mangrove expanses, Malay culture, and typical culinary. However, poor accessibility and lack of promotion hinder tourist visits. Strategies that can be applied are infrastructure improvements, training of local tour guides, and promotion through social media. The development of Kampung Tua Bakau Serip tourism village needs to pay attention to improving accessibility, involving local communities, and effective promotion so that tourist visits increase. The implementation of sustainable development strategies is important to realize an attractive and competitive tourist village.